Influence of Post Weld Heat Treatment on the HAZ of Low Alloy Steel Weldments - Mohideen, S. Rasool; Ahmad Zaidi, A.M. (International Journal of Integrated Engineering, 2010)
The heterogeneous nature of weldments demands an additional processing to retain and/or improve the joint properties. Heat Affected Zone, the zone Adjacent to the weld metal zone is critically affected by the sudden dissipation of heat from weld metal during welding. Toughness of this zone becomes weak as the grains get coarsened and the interface between the two regions is more prone to fracture. Post weld heat treatment is thus generally carried out on the weldments to relive the thermal residual stresses and to enhance the properties of welded joints. This paper discusses about the influence of post weld heat treatment on the fracture toughness of low alloy steel weldments. Fracture toughness of heat treated weldments was determined using standard CTOD test and the results were correlated.